Vulnerability of Urban Poor Women and Children to the Triple Burden of Malnutrition: A Scoping Review of the Sub-Saharan Africa Environment (Global Journal of Medical Research, 2017)
Research in sub-Saharan Africa (SSA) show a rapidly increasing trend in co-existence of hunger, micronutrients deficiency as well as overweight/obesity. The paper, vulnerability of urban poor women and children to the triple burden of malnutrition aims at exploring the situation of poor urban women and children in regard to the triple burden of malnutrition in SSA. 65 sources of information were retrieved for review. Many socio-economic and systemic factors appear to put poor urban women and children in SSA slumsat a greater risk of the triple burden of malnutrition.The triple burden of malnutrition has devouring effects on the growth and development of women and children. Evidence suggests high prevalence of the existence and effects of thethree tier complexity of malnutrition (hunger, micronutrients deficiency and over nutrition) among urban poor women and childrenin SSA.
Keywords: nutrition; nutrition in women; nutritional health; hunger; micronutrients deficiency; maternal and child nutrition health; overweight and obesity